PENGARUH PERMAINAN ULAR TANGGA 3 DIMENSI TERHADAP PERILAKU BERMORAL PADA USIA 5-6 TAHUN DI TK BINTANG CENDEKIA PEKANBARU - Wahyuni, Suci Sri; Zulkifli N, Zulkifli N; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aimed to determine the effect of 3 dimensional snake and ladder game on moral behavior at the age of 5-6 years in TK Bintang Cendekia Pekanbaru with methods one group pretest posttest design that experiments conducted on one group alone with no comparison group. As for the total sample of 20 children. Type of instrument used in this study is the observation and documentation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are there is an effect of 3 dimensional snake and ladder game on the moral behavior at the age of 5-6 years in TK Bintang Cendekia Pekanbaru. Retrieved tcount at 61,644 with sig 0.000, because sig <0.05 it can be concluded that there are significant differences in moral behavior in students before and after using the 3 dimensional snake and ladder game in learning. Hypothesis testing can be seen at tcount = 61,644 > ttable = 2,093024. It has been suggested that there is a significant difference in results between the pretest and posttest. The influence 3 dimensional snake and ladder game on moral behavior at the age of 5-6 years in TK Bintang Cendekia Pekanbaru is 56,58%.Key Words: Moral Behavior, 3 Dimensional Snake And Ladder Game